Refugees on their way into training : what support do they want? - Gei, Julia [Verfasser]; Matthes, Stephanie [Verfasser] (My University, 2017)
"The integration of refugees in training is currently one of the key socio-political challenges facing Germany. But how successful has this been so far? In the 2016 migrati-on study, which was conducted by the BIBB in cooperati-on with the Bundesagentur für Arbeit (BA) [Federal Em-ployment Agency], around 1,600 vocational education and training (VET) applicants from a refugee background were surveyed about their current situation and on their views and opinions. The results highlight the problems perceived by refugees on their way into training and the areas in which they would like to have support." (author's abstract ; BIBB-Doku)
Geflüchtete auf dem Weg in Ausbildung
Keywords: P 1.5 Migranten; G 1.3.1.1 Ausbildungsstellenmarkt; Flüchtling; Ausbildungsstellenbewerber; Berufsausbildung; Spracherwerb